Good Governance untuk Mendorong Pertumbuhan Ekonomi dan Perlindungan Hak-Hak Warga Negara - Hadi Susanto (Lembaga Administrasi Negara, 2017)
A common problem that often a rises is that the implementation of unplanned and uncoordinated governance often runs slowly as it has to priorize political consensus in the development of government systems. Our study observed the process of allocating proportional regional expenditures between consumptive routine spending and development spending that favor public interests so as to have a positive effect on economic growth. From the social and political side, especially in the midst of the unfavorable political situation, a compromise from ASEAN countries wa born to combine human rights implementation with the principles of governance in order to achieve the improvement of public services and the protection of human rights for the wider community. Keywords: human rights, good governance and clean government, economic growth